PENGARUH PROMOSI, CITRA MEREK DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN PENGGUNA APLIKASI BUKALAPAK DI KOTA BATAM - Chairul_Anan; Inda Sukati, Inda Sukati (LPPM Universitas Putera Batam, 2023)
This study aims to determine the effect of promotion, brand image and trust on purchasingdecisions of bukalapak application users in Batam City. This research uses quantitativemethods. There is also a population of a sample of 100 respondents who use thebukalapak application at least once. The sampling technique used is perposive samplingwith certain criteria to be sampled. Data processing using SPSS version 25. The analysismethod used in this research is descriptive statistical test, validity test and reliability test,classical assumption test, influence test, hypothesis testing. The analysis results of thestudy prove that the brand image variable with a significant value of 0.01 <0.05 and a trustvariable of 0.02 <0.05 has a positive and significant influence on purchasing decisions,while the promotion variable with a significant value of 0.166> 0.05 does not have apositive and significant influence on purchasing decisions